THE ROLE OF TRUST MEDIATES CUSTOMER RELATIONSHIP MANAGEMENT AND SERVICE QUALITY ON CUSTOMER LOYALTY - Adam, Fikri; Wahyuningsih; Sutomo, Maskuri (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
The purpose of this study was to empirically test and explain: (1) the effect of customer relationship management on the loyalty of credit customers at Bank Sulteng Ampana branch; (2) the effect of service quality on the loyalty of credit customers at the same branch; (3) the effect of customer relationship management on customer trust at Bank Sulteng Ampana branch; (4) the effect of service quality on the trust of credit customers at this branch; (5) the effect of trust on the loyalty of credit customers; (6) how customer relationship management influences loyalty through trust; and (7) how service quality influences loyalty through trust. This research uses a causality approach. Hypothesis testing was conducted with PLS-SEM, based on a sample of 100 ASN credit customer respondents. The analysis results show that: (1) customer relationship management significantly affects credit customer loyalty; (2) service quality does not significantly affect credit customer loyalty; (3) customer relationship management significantly influences customer trust; (4) service quality significantly impacts customer trust; (5) trust significantly affects credit customer loyalty; (6) customer relationship management significantly influences loyalty through trust; and (7) service quality significantly influences loyalty through trust